Ionic polymer metal composites for use as an organic electrolyte supercapacitor. (18th April 2019) - Lee, Pyoung-Chan; Hyun, Jung Eun; Jeoung, Sun Kyoung; Nam, Jae-Do; Hwang, Taeseon; Kim, Kwang Jin; Solasa, Krishna Chaitanya
Abstract: Choosing the right electrolyte for enhancement in energy storage and dissipation efficiencies of an electrochemical supercapacitor is a critical decision and a successful material choice could solve many issues faced by renewable energies such as wind and solar energy. Traditional aqueous electrolytes have been and continue to be used for their excellent electrolytic performance, but over past few decades, use of solid polymer electrolytes (SPEs) improved the performance of such devices by enhancing the power density and energy density. Platinum (Pt) incorporated ionic polymer metal composites (Pt-IPMCs) are being investigated for their applicability as solid polymer electrolyte (SPE) membrane for high-power supercapacitors as they have demonstrated improved performances in devices such as fuel cells, soft actuators etc. Pt nanoparticles were dispersed into a cubical Nafion membrane in a dense cluster (size distribution showing narrow). The Pt-IPMCs were tested using lithium hexafluorophosphate (LiPF6 ) in ethylene carbonate ((CH2 O)2 CO) and ethyl-methyl carbonate (C4 H8 O3 ) mixed in 2/1 volumetric ratio. Pt-IPMC resulted a lower internal voltage drop (0.15 V), higher ionic conductivity (0.46 mS cm −1 ), and higher specific capacitance (50.9 F g −1 ) compared with the commercial liquid electrolytes or Nafion 117. The average power density and energy density have improved by 19 and 17%, respectively by using Pt-IPMC electrolyte which could be ascribed to the decrease in the cell resistance or the increase of ionic conductivity. It should be noted that IPMC can be adopted as supercapacitor as well as soft actuator.